Murine 86-kDa heat shock protein gene and promoter - Dale, Emily C. (Cell Stress Society International, 1997)
The class of 90 kDa heat shock proteins (Hsp90) is among the most abundant heat shock proteins (Hsps) in eukaryotic cells. In vertebrates, Hsp90 is encoded by two distinct gene families giving rise to products of 84 and 86 kDa. In mice the expression of these two genes, hsp84 and hsp86, vary with respect to each other in responses to stress, and also in response to signals for growth and development. Therefore, as a step towards understanding the molecular basis for the differential regulation of these two genes, we have isolated and characterized genomic clones of the murine hsp86 gene and its 5′ flanking region. The gene is composed of eleven exons interrupted by 10 introns. The 5′ region contains consensus TATA, several stimulatory protein-1 binding site (SP1) elements as well as six consensus heat shock elements (HSE) 5′ of the transcription start site. An 806 bp fragment of the 5′ promoter region conferred constitutive expression upon a reporter gene and this expression was increased upon heat shock.